Effects of exclosures on woody species composition and carbon stocks: lessons drawn from the Central Rift Valley, Ethiopia - Degefa, H.; Tolera, M.; Kim, D.-G.; Mekuria, Wolde (Wiley, 2023)
Effects of exclosures on restoring degraded lands may vary with soil type, exclosure age, and conditions before the establishment of exclosures. Yet, studies investigating the effectiveness of exclosures in restoring degraded lands under different environmental conditions are lacking. This study aims at investigating the changes in woody species richness and diversity, and ecosystem carbon stocks after implementing exclosures in the Central Rift Valley, Ethiopia. Vegetation and soil data were gathered from 120 nested plots established in exclosures of eight and 30-years-old and adjacent grazing lands. Results showed that exclosures contained a higher number of economically important woody species compared to their respective adjacent grazing lands. However, the exclosures and respective adjacent grazing lands did not differ significantly in the diversity of tree and shrub species, and both the exclosures and adjacent grazing lands were dominated by few tree and shrub species. The older exclosure (30 years old) displayed significantly (p < 0.01) higher soil organic carbon and soil total nitrogen content and stocks than the adjacent grazing land, whereas the youngest exclosure (8 years old) did not show a significant difference in these variables. The results suggest that a longer time (e.g., =10 years) is needed to detect significant differences in soil organic carbon and total soil nitrogen. However, exclosures could bring considerable changes in woody species density in a relatively shorter period (e.g., =10 years) and support to restore degraded native woody species.